SIMD implementation of interpolation in algebraic soft-decision Reed-Solomon decoding - Boulianne, L.; Gross, W.J. (IEEE Workshop on Signal Processing Systems Design and Implementation, 2005, 2005)
The Koetter-Vardy algorithm is an algebraic soft-decision decoding algorithm for Reed-Solomon codes. Software implementations of the Koetter-Vardy algorithm are considered as part of a redecoding architecture that augments a hardware hard-decision decoder with soft-decision decoding software on an embedded processor. In this paper we investigate the implementation of the interpolation step of the Koetter-Vardy algorithm on SIMD processor architectures. A parallelization of the algorithm is given using the K'th order Horner's rule for parallel polynomial evaluation. The SIMD algorithm has a running time 2.5 to 4 times faster than a serial implementation on a DSP processor. To gain further speedup we propose a merged-SIMD architecture that calculates the Hasse derivative in parallel with the polynomial updates.